Pemeriksaan Karakteristik Simplisia dan Penapisan Fitokimia Simplisia dan Ekstrak Etanol Daun Suji (Draceana angustifolia (Medik.) Roxb.) - Ega Nirmala; Umi Yuniarni; Siti Hazar (UNISBA Press, 2022)
Abstract. Suji leaf (Draceana angustifolia) is one of the natural materials that has been widely used by people, one of them is used as a medicinal plant. Its manufacture as a medicinal plant can’t be separated from manufacture into the form of Simplicia. Each simplicia must be guaranteed in terms of quality, efficacy, and safety. Based on this, the problem in this research is formulated as follows: (1) What are the characteristics of suji leaf simplicia based on specific and non-specific parameters? (2) What are the groups of secondary compounds/metabolites contained in simplicia and ethanol extract of suji leaves? Determination of specific parameters including the determination of the water-soluble extract content and the determination of the ethanol-soluble extract content. Then for non-specific parameters including the determination of water content, determination of drying shrinkage, determination of total ash content, and determination of acid insoluble ash content. For phytochemical screening, the test is carried out by the color test method using specific reagents. The results of this research were: For the determination of the water-soluble extract content and the determination of the ethanol-soluble extract content were 12.67% and 5.84%, respectively. The results for the determination of the water content of 7.99%, the determination of drying shrinkage of 9.69%, the determination of the total ash content of 6.39%, and the determination of the acid insoluble ash content of 0.45%. The simplicia and ethanol extract of suji leaves contain several classes of chemical compounds/secondary metabolites including phenolic compounds and terpenoids. Abstrak. Daun suji (Draceana angustifolia) merupakan salah satu bahan alam yang telah banyak dimanfaatkan oleh masyarakat. Pemanfaatan daun suji juga sudah berkembang untuk digunakan sebagai tanaman obat. Dalam pembuatannya sebagai tanaman obat tidak lepas dari pembuatannya ke dalam bentuk simplisia. Setiap simplisia haruslah terjamin dalam hal mutu, khasiat dan keamanannya. Berdasarkan hal tersebut, maka rumusan masalah pada penelitian kali ini yaitu: (1) Bagaimanakah karakteristik simplisia daun suji berdasarkan parameter spesifik dan parameter non spesifik? (2) Apa sajakah golongan senyawa/metabolit sekunder yang terkandung pada simplisia maupun ekstrak etanol daun suji?. Penetapan parameter spesifik yang dilakukan meliputi penetapan kadar sari larut air dan penetapan kadar sari larut etanol. Kemudian untuk parameter non spesifik yang dilakukan yaitu penetapan kadar air, penetapan susut pengeringan, penetapan kadar abu total dan penetapan kadar abu tidak larut asam. Untuk penapisan fitokimia pada simplisia maupun ekstrak etanol daun suji dilakukan dengan metode uji warna dengan menggunakan pereaksi spesifik. Hasil dari penelitian ini adalah: Hasil penetapan kadar sari larut air dan penetapan kadar sari larut etanol berturut-turut adalah 12,67% dan 5,84%. Hasil untuk penetapan kadar air 7,99%, penetapan susut pengeringan 9,69%, penetapan kadar abu total 6,39% dan penetapan kadar abu tidak larut asam 0,45%. Pada simplisia dan ekstrak etanol daun suji mengandung beberapa golongan senyawa kimia/metabolit sekunder diantaranya adalah senyawa fenolik dan terpenoid.